A House for hermit crab - Carle, Eric (New York : Scholastic Inc, 1987)
Hermit Carbs live on the ocean floor. Their skin is hard except for the abdomen, which is soft.
Keywords: Houses--Fiction; Crabs--Fiction; Children stories